(untitled) (Bangladesh Pharmaceutical Journal, 2025)
Epidemiological knowledge of breast cancer continues to evolve but more needs to be learned. The amount of estrogen and progesterone that the breast epithelium is exposed to over time, primarily during the years of active ovarian activity, appears to be a major determinant of breast cancer risk in women. Possible approaches to primary prevention require a detailed understanding of the factors that influence the onset, regularity and quality of ovarian activity. The present study is a statistical cross-sectional survey. 126 respondents and 49 breast cancer patients were included with the information of knowledge and current life style practices towards cancer prevention. Age ranges, years of education information, gender, marital status and level of awareness related questions were included in the survey questionnaire. Most of the respondents were of age 40+ years, illiterate, female, married and unaware about the knowledge of breast cancer. Survival rate is a part of survival analysis. It is the percentage of people in a study or treatment group still alive for a given period of time after diagnosis. 49 individuals with breast cancer had a survival rate of 63% after 1-3 years, 35% after 1-2 years, and 2% after 4-6 years. Important baseline data on Bangladesh’s perception of avoidable cancer risk was supplied by this study. According to the study’s findings, lowering Bangladesh’s cancer burden will need an extensive cancer awareness campaign. Bangladesh Pharmaceutical Journal 28(1): 37-43, 2025 (January)